Exile's honor : a novel of Valdemar - Lackey, Mercedes (Lackey, Mercedes. Novel of Valdemar., 2003)
A former captain in the Army of Karse, Alberich must take a perilous stand when his long-hidden psychic talents are revealed, and he is rescued from certain death and chosen to serve the queen of Valdemar, Karse's archenemy.